Análise da qualidade de vida de doentes com Pseudo-Patela Baixa após Artroplastia Total do Joelho - Filipa Alexandra Crespo dos Santos (2022)
Background: Anterior knee pain is one of the most common causes of persistent complaints after total knee arthroplasty (TKA), with pseudo-patella baja (PPB) being one of the possible etiologies. There are few studies evaluating the impact of PPB after TKA. The purpose of this study is to evaluate the effect of PPB in primary TKA outcomes, particularly on health-related quality of life (HRQoL). Methods: Monocentric retrospective radiographic analysis of 612 knees submitted to TKA due to primary knee osteoarthritis, in patients >18 years old, with post-operative x-ray and minimal follow-up of 2 years. Primary analysis included evaluation of patellar height using Insall-Salvati and Blackburne-Peel ratios. Case group included 64 cases with PPB; control group was randomly assigned among patients with normal patellar height and Blackburne-Peel index ≥0.54. To assess HRQoL, the Short Form-12 questionnaire (SF-12) was applied. Anterior knee pain, Diabetes Mellitus Type 2 and the use of antidepressant medication after surgery were assessed. Results: There were no statistical differences between the PPB and non-PPB groups in median physical component score-12 (P=0.2). However, there was a significant difference between both groups regarding the median mental component score-12, depicting worse results among PPB patients (P=0.034). Anterior knee pain and antidepressant medication after the surgery were significantly more prevalent in the PPB group (P<0.001 and P=0.016). Conclusion: PPB appears to have a negative influence in clinical outcomes after TKA and it may condition an increased consumption of antidepressant medication after surgery.